2006
DOI: 10.1002/glia.20341
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes in 17β-estradiol treated mixed hippocampal cultures show attenuated calcium response to neuronal activity

Abstract: Glial cells in the brain are capable of responding to hormonal signals. The ovarian steroid hormone 17beta-estradiol, in addition to its actions on neurons, can directly affect glial cells. Estrogen receptors have been described on both neurons and astrocytes, suggesting a complex interplay between these two in mediating the effects of the hormone. Astrocytes sense and respond to neuronal activity with a rise in intracellular calcium concentration ([Ca(2+)](i)). Using simultaneous electrophysiology and calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…For example, estradiol can block cannabinoid-induced presynaptic inhibition of fast synaptic transmission in pro-opiomelanocortin neurons (Nguyen and Wagner 2006). Estradiol reduced the ability of neuronal activity to increase intracellular calcium levels in astrocytes in hippocampal cultures (Rao and Sikdar, 2006). This process is dependent upon activation of astrocyte mGluRs; consistent with this, the ability of 1-aminocyclopentane-1,3-dicarboxylic acid (ACPD), a broad-spectrum mGluR agonist, to increase astrocytic calcium levels was also decreased in estradiol-treated cultures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, estradiol can block cannabinoid-induced presynaptic inhibition of fast synaptic transmission in pro-opiomelanocortin neurons (Nguyen and Wagner 2006). Estradiol reduced the ability of neuronal activity to increase intracellular calcium levels in astrocytes in hippocampal cultures (Rao and Sikdar, 2006). This process is dependent upon activation of astrocyte mGluRs; consistent with this, the ability of 1-aminocyclopentane-1,3-dicarboxylic acid (ACPD), a broad-spectrum mGluR agonist, to increase astrocytic calcium levels was also decreased in estradiol-treated cultures.…”
Section: Discussionmentioning
confidence: 99%
“…When t-ACPD-evoked astrocyte [Ca 21 ] i responses were examined, it was observed that the number of astrocytes responding to t-ACPD and the amplitude of the response were lower in presence of estradiol, suggesting that estradiol rapidly inhibited astrocyte mGluRs. Effects of estradiol on mGluRs have been previously reported (Boulware et al, 2005;Hilton et al, 2006;Rao and Sikdar, 2006), and the rapid inhibitory actions described in our study could be instrumental in causing the impaired [Ca 21 ] i response seen in astrocytes around a stimulated cell.…”
Section: Discussionmentioning
confidence: 75%
“…Cumulative distributions were compared using Kolmogorov-Smirnov (K-S) test. (Rao and Sikdar, 2006). The fluorescence of the stimulated astrocyte recovered to baseline levels in all experiments indicating that mechanical stimulus did not irreversibly damage the cells.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations